Penerapan Senam Lansia untuk Mengatasi Gangguan Pola Tidur pada Lansia dengan Insomnia - Tsani, Revina Indria; Kurniawati, Ratna (JURNAL KESEHATAN KARTIKA, 2024)
Background: the number of elderly people in Indonesia in 2020 reached 9.92%, 67% of this number experienced insomnia and 78.1% of this number were women. Insomnia is characterized by difficulty falling asleep, waking up at night or too early and being sleepy during the day. Insomnia can cause physical, mental, quality of life and memory problems in the elderly. Elderly exercise was chosen because it can overcome insomnia and has a positive impact on physical fitness.Objective: to determine the effect of implementing elderly exercise to improve sleep patterns in elderly people with insomnia. Method: using a qualitative case study design with a case study research approach. Data was obtained through interviews and tests, and the results were presented in the form of a descriptive narrative. The subjects in this study were 2 people aged over 60 years who experienced mild to moderate insomnia for more than 3 weeks, didn’t take sleeping pills and were able to carry out activities independently. Implementation is carried out every two days 3 times, with a duration of 15 minutes per session. Results: after doing elderly exercise 3 times in 6 days for 15 minutes, the pattern Both subjects' sleep improved and their insomnia levels decreased from mild insomnia to no complaints of insomnia. Conclusion: the application of elderly exercise is effective in improving sleep patterns in elderly people who experience insomnia.